Islamic Economic Thoughts And Their Relevance In Society 5.0 Era Of Zainal Abidin Ahmad - Aufa Rizka Azzumi; Miswanto Miswanto; Naqiyah Naqiyah (Universitas 17 Agustus 1945 Semarang, 2023)
Islam has a concept of a universal, integral, and comprehensive way of life. This concept governs all aspects of human life, from the simple to the complex, including social, economic, political, educational, artistic, and cultural aspects. This research discusses the contribution of Islamic economics to national economic development, particularly in Indonesia, the largest Muslim-majority country in Asia. Islamic economics aims to create social justice, equitable income distribution, and economic sustainability within the context of Islam.The thoughts of Zainal Abidin Ahmad, a Muslim thinker from Indonesia, on Islamic economics, are explained in this research. Zainal Abidin Ahmad presents his views on Islamic economics as a distinct perspective from the popular capitalism and socialism of his time. Despite his comprehensive and profound thinking, Zainal Abidin Ahmad's ideas have received less attention from intellectuals, economists, and scholars. This article emphasizes the importance of studying and developing the thoughts of Zainal Abidin Ahmad in the current era. In this research, the researcher highlights the importance of studying and developing the ideas of Zainal Abidin Ahmad and previous Islamic economists relevant to the present era, particularly in the context of Islamic economics in the Society 5.0 era. Through in-depth research and study of these ideas, understanding will be enhanced, and relevant concepts of Islamic economics will be developed to address the challenges of the time.